The Relationship Between Ego Depletion and Prosocial Behavior of College Students During the COVID-19 Pandemic: The Role of Social Self-Efficacy and Personal Belief in a Just World - Li, Lu; Liu, Hairong; Wang, Guoping; Chen, Yun; Huang, Long (Frontiers in Psychology, 2022)
In the context of the COVID-19, we examined the relationship between college students’ ego depletion and their prosocial behavior. We explored the mediating role of social self-efficacy between ego depletion and prosocial behavior, we also examined the moderating role of personal belief in a just world in this relationship. 1122 college students completed the ego depletion questionnaire, prosocial behavior questionnaire, social self-efficacy questionnaire, and personal belief in a just world questionnaire. The current findings suggested that: (1) Social self-efficacy mediated the relationship between college students’ ego depletion and their prosocial behaviors. The ego depletion of college students could be used to predict their prosocial behavior through social self-efficacy. (2) Personal belief in a just world moderated the relationship between social self-efficacy and prosocial behavior.